P-283 Development of nurse practitioner role in hospice in-patient setting. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Finnegan, Rosemarie; Taylor, Jo; Roth, Lucy
Abstract : Background: Nurse Practitioners have a pivotal role in supporting clinical teams, enhancing patient care by bridging the gap between medical staff, nursing staff and other allied healthcare professionals in many healthcare settings. A clinical need was identified within our hospice team to support enhanced patient care. Aims: Nurse practitioners assess patients and develop appropriate management plans with the medical team and improve continuity of care. They aim to support and develop the skills of less experienced members of nursing staff. They work closely with all members of the multi-disciplinary team facilitating timely interventions and appropriate use of resources. Management and leadership commitments are integral to the role. The Nurse Practitioner, a senior nursing post, encourages career progression within the hospice nursing team. They act as a role model professionally, developing the confidence and competence within the nursing team more broadly. Method: Three nurses with advanced clinical skills were appointed as trainee nurse practitioners in January 2017. After one year, the role was evaluated using a short questionnaire circulated to all clinical and administrative staff. Specific questions were asked about impact on clinical practice, improvement of patient safety, improvement of education and learning needs and communication between team members. Respondents were also given the opportunity to write comments. Post-holders were encouraged to complete a reflective learning log. Results: A 72% response rate was received from questionnaires. Feedback was positive and informative. A thematic analysis was undertaken. The five identified themes have allowed us to develop the role and its integration within the clinical team. The post-holders have used reflection to identify individual learning needs. Conclusion: Due to the success of this innovative role, the organisation has continued to support the nurse practitioner role and also appointed two 'out reach' nurse practitioners to support patient care in the community.